UPAYA PENGENDALIAN KUALITAS PRODUK USAHA TEKSTIL DI PT. KTP UNTUK MEMINIMALISIR KECACATAN - Darmawan, Tedi; Rembulan, Glisina Dwinoor (Universitas Bunda Mulia, 2023)
Quality control is something that needs to be done by the company in order to minimize and prevent the smallest possible damage to the product. This research was conducted with the aim of controlling and improving the quality of PT. KTP, especially in children's clothing products, uses the DMAIC method (Define, Measure, Analyze, Improve and Control) and the SPC (Statistical Process Control) method to determine the factors causing product damage. From the results of the analysis performed using the control chart, it is known that it has a Control Limit (CL) of 0.0015 with an upper control limit of 0.0154 and a lower control limit of -0.0124. Based on these results, it is known that there is no data that exceeds the control limit or it can be said that the quality control in the company is still within the control limit. It is known that based on the Pareto diagram, the highest percentage of defective products is loose stitches by 48%, followed by cracked screen printing defects of 39%, and the last is torn defective products by 13%. Based on production data obtained from PT. KTP is known that the total number of production from September 2021 to August 2022 is 373,351 pcs with the number of defective products of 548 pcs. The DPMO (Defect Per Million Opportunity) value obtained on average is 1451.43 with a sigma value of 4.55. This shows that the level of sigma at PT. The ID card has a good sigma level which is the average USA industry standard but still needs further improvement.